Structural and functional MRI abnormalities of cerebellar cortex and nuclei in SCA3, SCA6 and Friedreich’s ataxia - Stefanescu, Maria Roxana; Dohnalek, Moritz; Maderwald, Stefan; Thürling, Markus; Minnerop, Martina; Beck, Andreas; Schlamann, Marc; Diedrichsen, Joern; Ladd, Mark E.; Timmann, Dagmar (Brain, 2015)
Data on the involvement of cerebellar nuclei in common hereditary ataxias are sparse. Stefanescu et al. reveal structural and functional abnormalities of cerebe
Gesehen am 22.06.2020